ANTHROPIZATION OF LANDSCAPES OF THE PRIPYAT RIVER BASIN - Zaleskyi, Ivan; Maiboroda, Kh. (Вісник Національного університету водного господарства та природокористування. Серія «Сільськогосподарські науки», 2020)
The present water management and environmental problems have acquired not only national but also international importance and have become one of the main factors of national security of Ukraine. The upper reaches of the Pripyat span an area of 2.2 thousand km2 from its source to the border with the Republic of Belarus. Hydrological features, terrain morphology, hydrological features, terrain morphology and anthropogenically altered lands are characterized with the necessary detail. An attempt has been made to calculate the anthropization value of the landscapes of the Pripyat River basin in the regional variant, according to the method of estimation of land changes by a certain kind of nature management by the coefficient of transformation of landscapes taking into account the depth and rank of transformation. The proposed variant of estimation of anthropogenic load on aquatic ecosystems will only strengthen the possibility of an objective scientific assessment of anthropogenesis.